Maharah Kalam: Bagaimana Mahasiswa Mempersiapkan Diri Untuk Menghadapinya? - Dewi Nuryaman, Adelina; Wahdah, Nurul; Marsiah (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2023)
This article reveals what must be prepared by Arabic Language Education students of IAIN Palangka Raya in semester 5 when they are going to attend lectures on al-kalam lii munaqasyah wal mujJadi, such as physical and mental preparation, obstacles experienced during lectures, and what linguistic and non-lingistic difficulties faced by students while practicing kalam. Considering that this lecture requires students to practice their speech up to 100% and in full for 2 credits. This study used a qualitative method with a phenomenological approach. Data were collected using research instruments in the form of interviews. To present data so that it is easy to understand, the data analysis steps used in this study are the Analysis Interactive Model from Miles and Huberman.